The Effect of The Low Hand Strategy on Students' Achievement in Mathematics and The Development of Their Science Operations Skills - Jamil, Sahar Abdul- Karim (Journal of Tikrit University for Humanities, 2022)
This research aims to identify (the effect of low-hand strategy on the achievement of the fourth scientific students in mathematics and developing their science operations skills). To achieve the research goal, the researcher formulated three zero hypotheses.To achieve the goal of the research, the researcher adopted the experimental design with two sets of pre-test and pre-test and intentionally selected a sample of the fourth scientific students from the Al-Furqan School for Girls of the General Directorate for Education of Salah al-Din / Tikrit for the academic year (2019-2020) for the purpose of applying the experiment.The sample consisted of (61) students with (31) students for the experimental group that studied the low-hand strategy, and (30) students for the control group that studied in the usual way.The researcher conducted the equivalence between the two research groups in the following variables: the student's chronological age calculated by months, the mathematics subject for the third intermediate grade, the educational level of the parents of the students, the educational level of the students' mothers, and the degree of the science operations skills test in the pre-test.To implement the experiment, the researcher identified the educational material that included the first and second semesters of mathematics for the fourth literary grade, and identified the main and sub-topics covered in the research subject, formulated the behavioral goals and prepared a number of studies plans according to each group.To achieve the goal of the research and test its hypotheses, the researcher prepared two tools, an achievement test, consisting of (40) paragraphs, and the second, a science operation skills test, consisting of (25) paragraphs, verifying their sincerity and reliability.The experiment lasted for one semester, which is the first semester of the academic year 2019-2020, and the data were processed using the appropriate statistical means and the following results appeared: There is a statistically significant difference at the level of significance (0.05) between the average scores of students of the experimental group who are studying mathematics using the low hand strategy, and the average scores of students of the control group who study according to the usual way in the achievement test. There is a statistically significant difference at the level of significance (0.05) between the average scores of students of the experimental group who are studying using the low hand strategy, and the average scores of students of the control group who are studying using the usual method in testing the skills of post-science operations. There is a statistically significant difference at the level of significance (0.05) between the average score of the experimental group students who are studying using low hand strategy in testing the skills of pre and post science. In the light of the results of the current research, the researcher developed a set of conclusions, recommendations and proposals